'I Feel Mad So I Be Bad': The Role of Affect, Dissatisfaction and Stress in Determining Responses to Interpersonal Deviance. (28th February 2018) - Michalak, Rebecca T.; Kiffin‐Petersen, Sandra A.; Ashkanasy, Neal M.
Abstract: Interpersonal deviance relates to a range of destructive individual and organizational outcomes. To date, however, scholars have largely failed to explore this issue from the perspective of the targeted individuals; and in particular how and why such negative outcomes manifest. To provide insights into this question, and based in principles of critical realism, we utilized semi‐structured in‐depth interviews to explore employees' interpersonal deviance experiences, their responses and determinants of response selections, including: (1) emotions and feelings; (2) dissatisfaction and stress. We found that the traditional model, where responses are driven by dissatisfaction and confined to exit, voice, loyalty and neglect (EVLN), is inadequate. We therefore extend the EVLN model to include retaliation (EVLN‐R) and identify a range of other responses, including venting and seeking social support for inclusion in the typology. Moreover, contrary to traditional theorizing, we found that responses were determined first and foremost by emotions and feelings, followed by stress, with dissatisfaction of little to no importance. We propose a new, multi‐dimensional response typology including self‐orientated responses and make suggestions for future research to test our typology, before closing with the implications for practice.